Arbuscular mycorrhizal fungi as a biological soil management practice for regulating soil carbon dynamics in agricultural soils: A global meta-analysis - Huawei Yang; Yuhang Zhang; Dingyi Liu; Yue Fan; Diwei Song; Pengju Li; Jingdan Yang; Xiaozhe Ma; Ruixin Bi; Shumin Li; Lingbo Meng (Soil and Tillage Research, 2026)

Decoding the Oxytocinergic and Behavioral Signatures of Milk Ejection - Wei Xiao; Qian Zheng; Yang Wang; Ying Yuan; Yuge Chen; Tianxing Zheng; Yuzhu Chen; Yijia Gao; Bingrui Song; Bin Zhang; Liyao Qiu; Linghui Zeng; et al. (Neuroscience Bulletin, 2026)

Investigating the correlation between major taste substances and volatile flavor substances in Lateolabrax japonicus (sea bass) under bloodletting conditions - Meijiao Gui; Mengli Han; Zhenhao Song; Yurui Zhang; Dajun Wang; Shumin Zhang; Wenzheng Shi (Food Control, 2026)

Carbon sequestration in soil affected by mineral-doped biochar: Roles of soil aggregate and microbial community - Rongchuan Ye; Yan Ma; Zixuan Wang; Ting Yang; Yanbin Du; Shumin Wu; Yanfang Feng; Lisha Wang; Wenjing Song (Journal of Cleaner Production, 2025)

Engineered interaction elements enable enhanced multi-enzyme assembly and cascade biocatalysis for indigo synthesis - Shumin Xu; Gao Song; Xianghui Qi; Guoshi Kan; J.A.A. Sampath Jayaweer; Yingfeng An (Bioresource Technology, 2025)

Revising the coal mining CH4 emission factor based on multiple inventories and atmospheric inversion approach at one of the world's largest coal production areas: Shanxi province, China - Xuejing Shi; Yiyi Peng; Shumin Wang; Yifan Zhang; Junqing Zhang; Hao Song; Yu Cui; Fan Sun; Huili Liu; Qitao Xiao; Ning Hu; Wei Xiao; et al. (Science of The Total Environment, 2025)

GWSM4C: A global wave surrogate model for climate simulation based on a convolutional architecture - Quan Jin; Xingjie Jiang; Feng Hua; Yongzeng Yang; Shumin Jiang; Chen Yu; Zhenya Song (Ocean Engineering, 2024)

pH-responsive Aminated mesoporous silica microspheres modified with soybean hull polysaccharides for curcumin encapsulation and controlled release - Shumin Wang; Shengnan Wang; Lina Yang; Peng Wang; Hong Song; He Liu (Food Chemistry, 2024)

Characterization of risks and pathogenesis of respiratory diseases caused by rural atmospheric PM2.5 - Ronghua Zhang; Xiaomeng Li; Xuan Li; Qin Zhang; Jiancai Tang; Zhenzhong Liu; Guiqin Song; Li Jiang; Fumo Yang; Jiawei Zhou; Hanxiong Che; Yan Han; et al. (Science of The Total Environment, 2024)

Three-dimensional subway alignment recreation considering tunnel construction gauges - Hao Pu; Shumin Xie; Taoran Song; Paul Schonfeld; Xianbao Peng (Tunnelling and Underground Space Technology, 2023)

Role and anti-inflammatory mechanisms of acupuncture and moxibustion therapy on pain relief through NOX-ROS-NLRP3 pathway in CCI rats models - Wang Jinying; Li Keming; Tang Hanqing; Zhang Xuqing; Fatima Muccee; Luo Xuan; Liu Yalin; Song Meiye; Zhang Shumin; Chandrabose Selvaraj; Sher Zaman Safi (Molecular Biology Reports, 2023)

Temporal-spatial Generation of Astrocytes in the Developing Diencephalon - Wentong Hong; Pifang Gong; Xinjie Pan; Zhonggan Ren; Yitong Liu; Guibo Qi; Jun-Liszt Li; Wenzhi Sun; Woo-Ping Ge; Chun-Li Zhang; Shumin Duan; Song Qin (Neuroscience Bulletin, 2023)
Astrocytes are the largest glial population in the mammalian brain. However, we have a minimal understanding of astrocyte development, especially fate specification in different regions of the brain. Through lineage tracing of the progenitors of the third ventricle (3V) wall via in-utero electroporation in the embryonic mouse brain, we show the fate specification and migration pattern of astrocytes derived from radial glia along the 3V wall. Unexpectedly, radial glia located in different regions along the 3V wall of the diencephalon produce distinct cell types: radial glia in the upper region produce astrocytes and those in the lower region produce neurons in the diencephalon. With genetic fate mapping analysis, we reveal that the first population of astrocytes appears along the zona incerta in the diencephalon. Astrogenesis occurs at an early time point in the dorsal region relative to that in the ventral region of the developing diencephalon. With transcriptomic analysis of the region-specific 3V wall and lateral ventricle (LV) wall, we identified cohorts of differentially-expressed genes in the dorsal 3V wall compared to the ventral 3V wall and LV wall that may regulate astrogenesis in the dorsal diencephalon. Together, these results demonstrate that the generation of astrocytes shows a spatiotemporal pattern in the developing mouse diencephalon.

Storage stability and interfacial rheology analysis of high-internal-phase emulsions stabilized by soy hull polysaccharide - Hui Yang; Shengnan Wang; Yan Xu; Shumin Wang; Lina Yang; Hong Song; Yutang He; He Liu (Food Chemistry, 2023)

Synthesis of magnetic nanocomposite Fe3O4@ZIF-8@ZIF-67 and removal of tetracycline in water - Xu Song; Jingqian Mo; Yuting Fang; Shumin Luo; Jingjing Xu; Xu Wang (Environmental Science and Pollution Research, 2022)

Target-oriented reverse time migration in transverse isotropy media - Liwei Song; Ying Shi; Shumin Chen; Weihong Wang; Xuan Ke (Acta Geophysica, 2021)

microRNA-499a promotes the progression and chemoresistance of cervical cancer cells by targeting SOX6 - Yibing Chen; Yucen Song; Yanjun Mi; Huan Jin; Jun Cao; Haolong Li; Liping Han; Ting Huang; Xiaofei Zhang; Shumin Ren; Qian Ma; Zhengzhi Zou (Apoptosis, 2020)

Spatial econometric analysis of carbon emission intensity in Chinese provinces from the perspective of innovation-driven - Song Liang; Jingfeng Zhao; Shumin He; Qingqing Xu; Xin Ma (Environmental Science and Pollution Research, 2019)

Adsorption performance and mechanisms of Pb(II), Cd(II), and Mn(II) removal by a β-cyclodextrin derivative - Mengjiao Zhang; Liyun Zhu; Changhua He; Xiaojun Xu; Zhengyang Duan; Shuli Liu; Mingyao Song; Shumin Song; Jiemei Shi; Yu’e Li; Guangzhu Cao (Environmental Science and Pollution Research, 2019)

Multiple steps determine CD73 shedding from RPE: lipid raft localization, ARA1 interaction, and MMP-9 up-regulation - Wei Zhang; Shumin Zhou; Guoping Liu; Fanqiang Kong; Song Chen; Hua Yan (Purinergic Signalling, 2018)

Human rotavirus strain Wa downregulates NHE1 and NHE6 expressions in rotavirus-infected Caco-2 cells - Honglang Chen; Lijun Song; Guixian Li; Wenfeng Chen; Shumin Zhao; Ruoxia Zhou; Xiaoying Shi; Zhenying Peng; Wenchang Zhao (Virus Genes, 2017)

Erratum to: Phosphocreatine protects against LPS-induced human umbilical vein endothelial cell apoptosis by regulating mitochondrial oxidative phosphorylation - Zhengwu Sun; Xiaoyan Lan; Anil Ahsan; Yalin Xi; Shumin Liu; Zonghui Zhang; Peng Chu; Yushu Song; Fengyuan Piao; Jinyong Peng; Yuan Lin; Guozhu Han; et al. (Apoptosis, 2016)

Phosphocreatine protects against LPS-induced human umbilical vein endothelial cell apoptosis by regulating mitochondrial oxidative phosphorylation - Zhengwu Sun; Xiaoyan Lan; Anil Ahsan; Yalin Xi; Shumin Liu; Zonghui Zhang; Peng Chu; Yushu Song; Fengyuan Piao; Jinyong Peng; Yuan Lin; Guozhu Han; et al. (Apoptosis, 2016)

Spy1 participates in the proliferation and apoptosis of epithelial ovarian cancer - Shumin Lu; Rong Liu; Min Su; Yingze Wei; Shuyun Yang; Song He; Xia Wang; Fulin Qiang; Chen Chen; Shuyang Zhao; Weiwei Zhang; Pan Xu; et al. (Journal of Molecular Histology, 2016)

Stem apex detoxification culture markedly improved several physiological characters of chrysanthemum ‘YUTAI’ - Yan Zhou; Yanyan Wang; Yanru Song; Ziyang Gao; Yanmei Liu; Lijuan Fan; Qing Hu; Shumin Gao (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)